2018
DOI: 10.14744/anatoljcardiol.2018.66181
|View full text |Cite
|
Sign up to set email alerts
|

Is There A Relationship Between Resistin Levels And Left Ventricular End-Diastolic Pressure?

Abstract: Objective:Resistin, a cysteine-rich peptide, is associated with atherosclerosis and diabetes. Resistin levels increase corresponding to coronary artery disease (CAD) and heart failure severity. Since resistin level tends to elevate with symptomatic heart failure, it is expected to be associated with left ventricular end-diastolic pressure (LVEDP). However, there is no relevant literature on the relationship between resistin levels and LVEDP. We aimed to evaluate the association between resistin levels and LVED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed that increased serum levels of resistin were associated with the IR, T2DM, AO, and CV diseases (226,227), while there were no significant correlations between resistin levels and echocardiographic parameters including LVEF, Gensini score index, angiographic parameters, and severity of atherosclerosis (228). Both the Framingham Offspring Study and the Health ABC Study have shown that the serum levels of resistin independently corresponded to a high risk of adverse CV outcomes and worsening kidney function among the patients with HF, but adiponectin levels did not (122,123).…”
Section: Resistinmentioning
confidence: 84%
“…Previous studies have revealed that increased serum levels of resistin were associated with the IR, T2DM, AO, and CV diseases (226,227), while there were no significant correlations between resistin levels and echocardiographic parameters including LVEF, Gensini score index, angiographic parameters, and severity of atherosclerosis (228). Both the Framingham Offspring Study and the Health ABC Study have shown that the serum levels of resistin independently corresponded to a high risk of adverse CV outcomes and worsening kidney function among the patients with HF, but adiponectin levels did not (122,123).…”
Section: Resistinmentioning
confidence: 84%